1994
DOI: 10.1002/anie.199415971
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition of C60 with γ‐Cyclodextrin

Abstract: \rilucs ( N M R . elemental analysis) were used for the determination of the lirst reflection in the X-ray I3Yh. ,~II,FC~II. <,/win. Itrt. Ed. Etrgi. 1993, 32. 1357 powdcr dill'raction patterns.[9] G . Albei-ti. hi. G Bernasconi. M. Casciola. Retrt.t. P / J / w~. 1989. fi. 245. [lo] G. tlonath. K . Kawazoe. J. Chiwi. Eng. Jpn. 1983, 16. 470. [I I ] Stirtiice iirciis \$ere investieated by BET analysis. The presence of mesopores uah cxcluded hy the rcversihil~ty of the adsorption isotherms. Information on the ~o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
170
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(175 citation statements)
references
References 21 publications
4
170
1
Order By: Relevance
“…The discovery led to extensive studies on various CD complexes related to tools for nanocomposite [4] and a novel reducing reagent [5]. Geckeler and Constabel reported that cucurbit [7]uril 12 also forms a complex with C 60 by solid-liquid reaction (Figure 3.4) [6]. In these complexes, the attractive interactions between the heteroatoms as an n-donor and the fullerene surface should be operative [7], but the main driving force of the complexes should be hydrophobic effect.…”
Section: Simple Traditional Hostsmentioning
confidence: 99%
“…The discovery led to extensive studies on various CD complexes related to tools for nanocomposite [4] and a novel reducing reagent [5]. Geckeler and Constabel reported that cucurbit [7]uril 12 also forms a complex with C 60 by solid-liquid reaction (Figure 3.4) [6]. In these complexes, the attractive interactions between the heteroatoms as an n-donor and the fullerene surface should be operative [7], but the main driving force of the complexes should be hydrophobic effect.…”
Section: Simple Traditional Hostsmentioning
confidence: 99%
“…Preparation of γ-Cyclodextrin Bicapped C 60 [(γ-CyD) 2 /C 60 ] and C 60 (OH) 24 Solution γ-Cyclodextrin bicapped C 60 [(γ-CyD) 2 /C 60 ] was prepared by the method of Yoshida et al (28,29) with some modification. Briefly, a mixture of C 60 (40.0 mg; 55.6 μmol) and γ-cyclodextrin (120.0 mg; 92.5 μmol) was stirred in a water/toluene (16/6 v/v) mixture at 118 °C for 48 h, and then, γ-cyclodextrin (60.0 mg; 46.3 μmol) was added twice more at 48 h intervals.…”
Section: Chemicalsmentioning
confidence: 99%
“…Then, the solution was filtered/sterilized through a 0.22 μm cellulose acetate membrane to remove the insoluble materials (C 60 released from unstable complexes) and bacteria. The concentration of the solution was determined from its absorbance at 332 nm [log ε = 4.63 (29)]. This solution was prepared fresh before each use because the complex was unstable in water.…”
Section: Chemicalsmentioning
confidence: 99%
“…20) Despite numerous studies on the radical scavenging activity of water-soluble fullerenes, little is known about the comparative assay of fullerenes versus -carotene, the latter of which has frequently served as a reference compound in determining antioxidant activity. [21][22][23][24] In the present study, the antioxidant activity of supramolecular water-soluble fullerenes, viz., polyvinylpyrrolidone (PVP)-entrapped C 60 25) and -cyclodextrin (CD)-bicapped C 60 , [26][27][28][29] as shown in Fig. 1, was kinetically evaluated by means of coupled autoxidation of linoleic acid and -carotene.…”
mentioning
confidence: 99%